Answer the question Pls

Answer The Question Pls
Answer The Question Pls

Answers

Answer 1

Answer:

The first option:

Prove that the area of the two small squares combined is equal to the area of the larger square

Step-by-step explanation:

The Pythagorean Theorem in an equation would be:

a² + b² = c²

Where:

c = hypotenuse (longest side of the triangle)

a and b = two other legs of the triangle

The theorem states that the sum of the squares of the shorter sides is equal to the square of the longest side in a right triangle or a triangle that has a right angle (90°)

Let's say that we have a right triangle with the lengths of 3cm , 4cm, and 5cm.

(3cm)² + (4cm)² = (5cm)²

9cm² + 16cm² = 25cm²

25cm² = 25cm²

Look at the attached image to see what happens when we draw the squares of each leg.

Answer The Question Pls

Related Questions

Find values of a and b that make the following equality into identity:

Answers

Answer:

1. [tex]a=b=\dfrac{3}{4}[/tex]

2. [tex]a=-3,\ b=3[/tex]

Step-by-step explanation:

1. Given:

[tex]\dfrac{3x}{(x-2)(3x+2)}=\dfrac{a}{x-2}+\dfrac{b}{3x+2}[/tex]

To find a and b, add two fractions in right side:

[tex]\dfrac{a}{x-2}+\dfrac{b}{3x+2}\\ \\=\dfrac{a(3x+2)+b(x-2)}{(x-2)(3x+2)}\\ \\=\dfrac{3ax+2a+bx-2b}{(x-2)(3x+2)}\\ \\=\dfrac{(3a+b)x+(2a-2b)}{(x-2)(3x+2)}[/tex]

So,

[tex]\dfrac{3x}{(x-2)(3x+2)}=\dfrac{(3a+b)x+(2a-2b)}{(x-2)(3x+2)}[/tex]

Two fractions with same denominators are equal when they have equal numerators, so

[tex]3x=(3a+b)x+(2a-2b)[/tex]

Equate coefficients:

[tex]At\ x:\ \ 3=3a+b\\ \\At \ 1: 0=2a-2b[/tex]

From the second equation:

[tex]a=b[/tex]

Substitute it into the first equation:

[tex]3b+b=3\\ \\4b=3\\ \\b=\dfrac{3}{4}[/tex]

Hence,

[tex]\dfrac{3x}{(x-2)(3x+2)}=\dfrac{\frac{3}{4}}{x-2}+\dfrac{\frac{3}{4}}{3x+2}[/tex]

2. Given:

[tex]\dfrac{3}{x^2-5x+6}=\dfrac{a}{x-2}+\dfrac{b}{x-3}[/tex]

Note that [tex](x-2)(x-3)=x^2-3x-2x+6=x^2-5x+6[/tex]

To find a and b, add two fractions in right side:

[tex]\dfrac{a}{x-2}+\dfrac{b}{x-3}\\ \\=\dfrac{a(x-3)+b(x-2)}{(x-2)(x-3)}\\ \\=\dfrac{ax-3a+bx-2b}{(x-2)(x-3)}\\ \\=\dfrac{(a+b)x+(-3a-2b)}{(x-2)(x-3)}[/tex]

So,

[tex]\dfrac{3}{(x-2)(x-3)}=\dfrac{(a+b)x+(-3a-2b)}{(x-2)(x-3)}[/tex]

Two fractions with same denominators are equal when they have equal numerators, so

[tex]3=(a+b)x+(-3a-2b)[/tex]

Equate coefficients:

[tex]At\ x:\ \ 0=a+b\\ \\At \ 1: 3=-3a-2b[/tex]

From the first equation:

[tex]a=-b[/tex]

Substitute it into the second equation:

[tex]-3(-b)-2b=3\\ \\3b-2b=3\\ \\b=3\\ \\a=-3[/tex]

Hence,

[tex]\dfrac{3}{x^2-5x+6}=\dfrac{-3}{x-2}+\dfrac{3}{x-3}[/tex]

Final answer:

To turn an equality into an identity, you would find values for 'a' and 'b' that work for all values of 'x'. The process involves equating coefficients and solving the resulting equations. Without specific equations, we must rely on general methods, such as using the quadratic formula when 'c' is known.

Explanation:

Finding Values of a and b

To make the equality into an identity, you'll typically want to find values of 'a' and 'b' that satisfy the given equations for all values of 'x'. It seems like part of your question is missing, as we would need the specific equations to give a precise answer. However, the process involves equating coefficients of the same powers of 'x' from both sides of the equation and solving the resulting system of equations.

For example, if you have an equation of the form ax2 + bx + c = 0 and you want to make it an identity, you can find 'a' and 'b' by applying the quadratic formula when 'c' is given.

In the case of a quadratic equation ax2 + bx + c = 0, you can determine 'a' and 'b' by solving:

-b ± √(b2 - 4ac) / (2a)

Which simplifies down when given specific constants, as shown by the example where a = 3, b = 13, and c = -10. This yields two possible solutions for 'x' which can verify the values of 'a' and 'b'.

If an equation already has set constants like a = 1.00, b = 10.0, and c = -200, then the equation is already defined, and the values are given.

Please help! :) Need answer fast!

Answers

Answer:

x = 3

y = 2

Step-by-step explanation:

When 2 triangles are congruent, they will have exact same 3 sides length and exact same 3 angles measure.

So we can say:

-2x + 6y = 6

and

-7x + 8y = -5

Let's multiply first equation by 7 and 2nd equation by -2, to get:

7 [-2x + 6y = 6] = -14x +42y = 42

and

-2 [-7x + 8y = -5] = 14x - 16y = 10

Now adding these 2 new equations and solving for y:

-14x +42y = 42

14x - 16y = 10

----------------------

26y = 52

y = 52/26

y = 2

Now we put y = 2 into 1st equation (or any other) and solve for x:

-2x + 6y = 6

-2x + 6(2) = 6

-2x + 12 = 6

6 = 2x

x = 6/2

x = 3

What is the range of possible sizes for side x?

Answers

Check the picture below.

the idea being that sides of 2.5 andd 8 are fixed, what's are the possible lengths of "x"?

well, if we open the fixed sides, we'll end up with a 3rd side of 2.5 + 8 = 10.5, however if "x" is ever 10.5, the figure will become a flat-line and we'd be losing the triangle.

and if we close the fixed sizes, the longest "x" could be is 8 - 2.5 = 5.5, but the same, it can't be 5.5 exactly otherwise the figure will turn to a flat-line.

5.5 < x < 10.5.

Answer:

5.5 < x < 10.5

Step-by-step explanation:

Khan

How to write 40+5\10

Answers

Answer:

4 tens + 5 tenths

Step-by-step explanation:

40+5\10= 40+1/2=40.5

(1/5)^(x+1)=125 how do I solve this?​

Answers

Answer:

X=-4

Step-by-step explanation:

In the attached file

Solve: In 2x + In 2 = 0
DONE

Answers

Answer:

[tex]x=\frac{1}{4}[/tex]

Step-by-step explanation:

We can use some logarithmic rules to solve this easily.

Note: Ln means [tex]Log_e[/tex]

Now, lets start with the equation:

[tex]ln(2x) + ln(2) = 0\\ln(2x) = -ln(2)[/tex]

Writing left side with logarithmic base e, we have:

[tex]Log_{e}(2x) = -ln(2)[/tex]

We can now use the property shown below to make this into exponential form:

[tex]Log_{a}b=x\\means\\a^x=b[/tex]

So, we write:

[tex]Log_{e}(2x) = -ln(2)\\e^{-ln(2)}=2x[/tex]

We recognize another property of exponentials:

[tex]a^{bc}=(a^{b})^{c}[/tex]

So, we write:

[tex]e^{-ln(2)}=2x\\(e^{ln(2)})^{-1}=2x[/tex]

Also, another property of natural logarithms is:

[tex]e^{(ln(a))}=a[/tex]

Now, we simplify:

[tex](e^{ln(2)})^{-1}=2x\\(2)^{-1}=2x\\\frac{1}{2}=2x\\x=\frac{\frac{1}{2}}{2}\\x=\frac{1}{4}[/tex]

This is the answer.

What is 3 ÷ 2/5? The quotient is 7 and _____



HELP PLEASE

Answers

Answer:

Your answer is 15/2 i hoped i helped

Step-by-step explanation:

Answer:

1

Step-by-step explanation:

3×5/2

15/2

The remainder is 1

What is s=(n - 2)180

Answers

Answer:

angle sum of a triangle’Formula

Step-by-step explanation:

N stands for the number of edges, - 2 is the result after finishing, 2 has no special significance. Because the sum of outer angles is a constant n-edge shape with 360 degrees, take n flat angles 180n = inner angle and + 360, so the sum of inner angles = 180n-360 = 180 (n-2)

That formula tells you what is the sum of the interior angles of a polygon with n sides.

So, for example, a triangle has n=3 sides, and in fact the sum of its interior angles is

[tex](3-2)\cdot 180=180[/tex]

As another example, the sum of the interior angles of a polygon with 15 sides is

[tex](15-2)\cdot 180=13\cdot 180=2340[/tex]

megan has a rope that is 15 feet in length she cuts the rope into 4 pieces how long is each section of to ​

Answers

Answer:

3.75

Step-by-step explanation:

You take your 15 feed and divide it by 4 for the four pieces she cuts the rope into giving you with each section of the cut rope being 3.75 in.

The length of each piece is 3.75 feet long.

What is Equation Modelling?

Equation modelling is the process of writing a mathematical verbal expression in the form of a mathematical expression for correct analysis, observations and results of the given problem.

We have Megan who has a rope that is 15 feet in length and she cuts the rope into 4 pieces.

Assume that the length of each piece is x ft. Then -

4x = 15

x = 15/4

x = 3.75 ft

Therefore, the length of each piece is 3.75 feet long.

To solve more questions on equation modelling, visit the link below-

brainly.com/question/6593383

#SPJ5

a
The hypotenuse of a right triangle is 15 centimeters long. One leg is
9 centimeters long. How long is the other leg?

Answers

The other leg is 12cm long.

Step-by-step explanation:

Given,

Hypotenuse = c = 15cm

One leg = a = 9cm

Other leg = b

As the triangle is right angled, therefore, using Pythagoras theorem;

[tex]a^2+b^2=c^2\\(9)^2+b^2=(15)^2\\81+b^2=225\\b^2=225-81\\b^2=144\\[/tex]

Taking square root on both sides;

[tex]\sqrt{b^2} =\sqrt{144} \\b=12\ cm[/tex]

The other leg is 12cm long.

Keywords: triangle, square root

Learn more about triangles at:

brainly.com/question/5461619brainly.com/question/5510873

#LearnwithBrainly

What is the degree of the expression that represents the perimeter of this triangle ???? PLEASE HELP ME

Answers

Answer:

1.

Step-by-step explanation:

The perimeter is a length - degree 1.

The degree of the expression that represents the perimeter of this triangle is 2

How to determine the degree

The formula for calculating the perimeter of a triangle is expressed as;

P = a + b + c

Such that the parameters are denoted as;

P is the perimeter of the trianglea, b and c are the lengths of the side of the triangle

From the diagram shown, we have that;

Perimeter = 2x²+ 2x ² + 4x + 5

collect the like terms, we get;

Perimeter = 4x²+ 4x + 5

Learn about perimeter at:https://brainly.com/question/16596982

#SPJ3

13m-7-10m=2? I need help

Answers

13M-7-10m = 2
3m-7=2
3m=2+7
3m=9
M=3

Answer:

[tex]\displaystyle 3 = m[/tex]

Step-by-step explanation:

2 = −7 + 3m

+ 7 + 7

__________

[tex]\displaystyle \frac{9}{3} = \frac{3m}{3} \\ \\ 3 = m[/tex]

I am joyous to assist you anytime.

complete the linear equation

Answers

Answer:

[tex]y=-30x[/tex]

Step-by-step explanation:

The intercept of the function is the value of y when x=0. In this particular case, when x=0, y=0, then the intercept is y=0.The slope of the function must tell us what is the change in y when x changes.  When x changes in one unit (from x=0 to x=1), y takes the value of y=-30, y=1x(-30). When x takes the value of x=2, y takes the value of y=-60, then y=2x(-30), and when x=3, y=3x(-30)=-90.This means that y always takes the value of -30x. Then the slope is -30, which is the rate of change of y as x changes.

Simplify x² + 3x + 2/X +1

Answers

Final answer:

To simplify the expression x² + 3x + 2 / X + 1, factor the numerator and denominator expressions separately. The simplified form of the expression is (x + 2) / 1.

Explanation:

To simplify the expression, x² + 3x + 2 / X + 1, we can use the factoring method. First, we factor the numerator expression. The expression x² + 3x + 2 can be factored as (x + 2)(x + 1). Then, we factor the denominator expression X + 1. So, the simplified form of the expression is (x + 2) / 1.

Learn more about expression

https://brainly.com/question/723406

#SPJ11

Luis left a 20% tip on a $30.00 food bill. How much did he leave for the tip?

Answers

Answer:

He left $6 for the tip.

Step-by-step explanation:

20%=0.2

0.2*30=6

Write an equation in point slope form (12,7) m=-2

Answers

Answer:

y= -2x+31

Step-by-step explanation:

Y=-2x+B

7=-2(12)+B

7=-24+B

7+24= (-24+24)+B

31=B

Y=-2x+31

Hope it helps!!

Factor each expression 12x + 24

Answers

Answer:

12(x+2)

Step-by-step explanation:

Factor a 12 out of

12x + 24

12 goes into 12 once

12 goes into 24 twice

= 12(x+2)

HELP ASAP!!! 100 POINTS!!!

1. It takes the earth 24 h to complete a full rotation. It takes Mercury approximately 58 days, 15 h, and 30 min to complete a full rotation. How many hours does it take Mercury to complete a full rotation? Show your work using the correct conversion factors.

Answers

Answer:

HERE IS THE ANSWER 1407.5 hours

Step-by-step explanation:

The supermarket has pie filling
on sale for $1.19. Mom bought
four cans. If she gave the clerk
$ 10, what is her change?

Answers

Answer:

$5.24

Step-by-step explanation:

If Mom bought 4, she bought [tex]$1.19*4=$4.76[/tex] worth of pie filling. Since she paid $10, she needs [tex]$10-$4.76=$5.24[/tex] change

her change is $5.24

if you do $1.19 times 4 which is $4.76
then $10 minus $4.76 is $5.24

10 - (1.19 x 4)

2x - 2(4x-3) = 6 - 6x​

Answers

Answer:

x=

Step-by-step explanation:

Open parenthesis first:

2x-8x+6=6-6x

Combine like terms:

-6x+6=6-6x

Then move all like terms to one side:

6-6=-6x+6x

Simplify:

0=0

0=0 is true, so x can equal any number and the result will be true. (Like the number 4, for example. If x was 4, you would get 4=4.)

~Stay golden~ :)

Simplify the square root of 41

Answers

Answer:

it's already in it's simplest form

Step-by-step explanation:

Answer:

the answer would still be the same as the problem because if you use prime factorization it would still be the square root of 41  

Step-by-step explanation:

[tex]\sqrt{41\\[/tex]

Please answer this correctly

Answers

28 to nine means it is 8:32 ( to get this you subtract 28 from 9.) ( its saying there are 28 minutes left until it is 9)

add 8 hours

= 8+ 8 = 16

well we arent talking about military time sooo 16-12 = 4

4 : 32 and you need to add the 59 so

32+ 59 = 91

91 - 60 = 31 (dont forget to add the extra 1 hour because we subtracted 60 minutes :). )

so the correct time will be 5: 31

Answer: 5:31

Step-by-step explanation:

28 minutes to 9 is 8:32

8 hours and 59 minutes later it would be 5:31

How many solutions does this system have?

Answers

Answer:

x=0, exactly one solution.

Step-by-step explanation:

y=3x+3

y=-2x+3

-----------

3x+3=-2x+3

3x-(-2x)+3=3

3x+2x+3=3

5x+3=3

5x=3-3

5x=0

x=0/5

x=0

At present Asha's age (in years) is two more than the square of her daughter Nisha's age (in years). When Nisha grows to her mother's present age, Asha's age would be one year less than 10 times the present age of Nisha. Find the present age of Asha and Nisha

Answers

Answer:

Asha's present age is 27 years and Nisha's present age is 5 years.

Step-by-step explanation:

Let the present age of Nisha be [tex]x[/tex] years.

As per question, Asha's present age is 2 more than the square of Nisha's age.

[tex]\therefore[/tex] Asha's present age = [tex]x^2+2[/tex]

Now, Nisha will reach her mother's age after [tex]x^2+2-x[/tex] years.

Therefore, age of Asha after [tex]x^2+2-x[/tex] years will be = [tex]x^2+2+x^2+2-x=2x^2-x+4[/tex]

Now, as per question,

[tex]2x^2-x+4=10x-1\\2x^2-x-10x+4+1=0\\2x^2-11x+5=0\\2x^2-x-10x+5=0\\x(2x-1)-5(2x-1)=0\\(2x-1)(x-5)=0\\x=\frac{1}{2}\ or\ x=5[/tex]

As age can't be in fraction, we consider the present age of Nisha as 5 years. So, Asha's present age is [tex]x^2+2=5^2+2=25+2=27[/tex] years.

Therefore, Asha's present age is 27 years and Nisha's present age is 5 years.

Can you help me please?

Answers

Answer:

i believe you answer would be B. 3

Step-by-step explanation:

For the following exercises, use the function f represented in table 14 below

Evaluate f(3)

Solve f(x)=1

Answers

f(3)=53 and for f(x)=1; x=2
Final answer:

Without Table 14, a specific answer can't be provided. But generally you would find the y value when x is 3 for f(3), or find the x value when y is 1 for f(x)=1.

Explanation:

This question pertains to the evaluation of f(3) and solving for f(x)=1 within the given function f that's represented in Table 14. Unfortunately, as the Table 14 isn't provided, I can't give a specific answer. However, generally, to evaluate f(3), find the pair where the x value is 3; the corresponding y (or f(x)) value is the result of f(3). To solve f(x)=1, look for the pair in the table where the f(x) (or y) value is 1; the corresponding x value is the solution for f(x)=1.

Learn more about Function Evaluation here:

https://brainly.com/question/12056604

#SPJ2

if 3 miles is equal to 4828.05 miles, how many meters are in 5 miles​

Answers

There are 8046.75 meters in 5 miles

Step-by-step explanation:

Method 1:

First of all we have to calculate the unit conversion.

Assuming that 3 miles is equal to 4828.05 meters

We have to find that how many meters make one mile

So,

3 miles = 4828.05 meters

[tex]1\ mile=\frac{4828.05}{3}\\=1609.35\ meters[/tex]

Now we know that:

[tex]1\ mile=1609.35\ meters\\5\ miles=1609.35*5 = 8046.74\ meters[/tex]

Method 2:

We can also use ratios to find the number of meters in 5 miles as:

3:4828.05::5:x

where x is the number of meters in 5 miles

[tex]\frac{3}{4828.05}=\frac{5}{x}\\x=\fac{5*4828.05}{3}\\=8046.75\ meters[/tex]

Hence,

There are 8046.75 meters in 5 miles

Keywords: Conversions, Units

Learn more about conversions at:

brainly.com/question/10699220brainly.com/question/10703930

#LearnwithBrainly

The length of a rectangle is 9 cm more than its
width. If the area of the rectangle is 36 cm2,
what are the dimensions? Justify your answer.

Answers

= 4 = x²

x = Answer: Length= 11 , Brteadth = 2

Step-by-step explanation: Let the breadth of the rectangle be x

length = 9 + x

area = 36 cm²

A.T.Q

36cm² = 9x*x

36 = 9x²

36/9 = 4 = x²

x = root of 4

x= 2

Therefore , breadth of rectangle is 3cm and length is 12 cm

verification:

l*b = 12*3 = 36cm²

Beth read a total of 12 books over 7 months.
If Beth has read 84 books so far, how many months has she been with her book club?
Solve using unit rates.

Answers

She has been with her book club for 49 months.

Step-by-step explanation:

Books read = 12 books

Time period = 7 months

Therefore,

12 books = 7 months

1 book = [tex]\frac{7}{12}\ months[/tex]    

Books read so far = 84 books

Total time period = x

84 books = x months

1 book = [tex]\frac{x}{84}\ months[/tex]

Using both unit rates;

[tex]\frac{x}{84}=\frac{7}{12}\\x=\frac{7}{12}*84\\x=\frac{588}{12}\\x=49\ months[/tex]

She has been with her book club for 49 months.

Keywords: Unit rates, multiplication

Learn more about multiplication at:

brainly.com/question/10699220brainly.com/question/10703930

#LearnwithBrainly

need help as soon as possible !! ​

Answers

Answer:

x = 64

Step-by-step explanation:

The sum of the interior angles of a quadrilateral = 360°

Sum the given angles and equate to 360

x + 2x + 114 + x - 10 = 360, that is

4x + 104 = 360 ( subtract 104 from both sides )

4x = 256 ( divide both sides by 4 )

x = 64

Your Answer would be x = 64
Other Questions
Li reads 64 pages of her book on day one. On day two shereads 17 pages. Li says the sum of 64 and 17 is 71 pages.Explain what Li did wrong. How many pages did Li read in all?Show your work.Li readpages in all. On a standardized test, Paul answered the first 22 questions in 5 minutes. There are 77 questions on the test.If he continues to answer questions at the same rate, how long will it take him to complete the testfrom start to finish? An ant moves forward 18.2 inches in one hour. It turns around and crawls 13.5 inches in the next hour. Finally, in the third hour, it turns around again and crawls 5.1 more inches. How much forward progress did the ant make in 3 hours? At the end of a three-year study, Susan finds that 12 percent of her participants did not take part in the final survey because they moved away. In research terms, Susan is experiencing a _____ problem. Good health, a desire to remain sexually active, access to a partner, and a conducive environment contribute to positive sexual experiences. Which physiological change occurs in women related to their sexual functioning? please can someone solve this physics question with a good explenation. Which shows the equation 6x + 4y = 10 written in slope-intercept form?A. y= -3/2x + 5/2B. y= -4/6x + 5/3C. y= -4x + 4D. y= -6x + 10I need it explained please so that I'm able to solve questions like this. [tex][/tex] What makes sponges unique among animals? What would a plot of p versus 1/v look like for a fixed quantity of gas at a fixed temperature? Which of the following characterizes an MNE from a non-MNE? a. It enters foreign markets through FPI. b. It exports or imports with or without FDI. c. It enters foreign markets via non-equity modes. d. It enjoys OLI advantages. Find the sum of the side lengths.(d + 5) + (d + 5) + (d + 5) A box is filled with 4 red cards, 4 green cards, and 6 brown cards. A card is chosen at random from the box. What is the probability that the card is not green?Write your answer as a fraction in simplest form. A lift (elevator) is operated by an electric motor. It descends from the 10th floor to the 2nd floor at a constant speed. What is the main energy transformation during this journey?#1gravitational potential energy kinetic energy.#2electrical energy kinetic energy.#3kinetic energy thermal energy.#4electrical energy thermal energy. Chemistry Smart people please help me out I will give you the brainiest I need help!Magnesium has two valence electrons and oxygen has six valence electrons. The electronegativity difference between the two elements is 2.13.How can the octet rule be used to explain the bonding between magnesium and oxygen?Oxygen needs access to two electrons to satisfy the octet rule. Magnesium prefers to lose two valence electrons to satisfy the octet rule. Oxygen can remove two electrons from magnesium, forming ions; leading to an ionic bond.Oxygen needs to lose six electrons to satisfy the octet rule. Magnesium needs access to six valence electrons to satisfy the octet rule. Magnesium can remove six electrons from oxygen, forming ions and leading to an ionic bond.Oxygen needs access to two electrons to satisfy the octet rule. Magnesium prefers to lose two valence electrons to satisfy the octet rule. Magnesium and oxygen can share two electrons, leading to a covalent bond.Oxygen needs to lose six electrons to satisfy the octet rule. Magnesium needs access to six valence electrons to satisfy the octet rule. Magnesium and oxygen can share six electrons, leading to a covalent bond. connotation__________the implied or suggested meaning connected with a word denotation: the dictionary meaning of a word literal meaning___________ limited to the simplest, ordinary, most obvious meaning figurative meaning________associative or connotative meaning; A study was conducted to identify the relationship between the hours of practice put in by the University at Buffalo football team and the success they had in games won. The Pearson's correlation coefficient was found to be .78. What type of relationship does this represent- positive or direct/negative or inverse? What is the strength of this relationship- weak, moderate, or strong? A. Direct, strong B. Direct, moderate C. Inverse, strong D. Inverse moderate. Some positive integer, x, results in a square number when 64 is taken away from it, and when 25 is added to it. Find x. Cmo va a ser el verano en el desierto?Espero que haga firo y nieve.Espero que no haga mucho calor.Espero que el agua est fresca y un poco fra.Espero que hayan muchos pescados en el aguaQuiero tener un buen viaje. The even division of 12 by 1, 2, 3, 4, and 6 (is, are) possible John belongs to a labor union. He believes a few key people run the union by meeting secretly and making decisions without informing other members or allowing them to fully participate in the meetings. If John's suspicions are correct, the union is violating provisions of the __________ Act. A) Landrum-Griffin B) Fair Labor Standards C) Taft-Hartley D) Wagner